Risk management in the pharmaceutical industry in Slovenian companies - Bucalo, Nina (Logistics and sustainable transport, 2017)
The pharmaceutical industry is one of the most competitive businesses in the world. Supply chain in this industry has been directed towards the production of large batches to avoid lack of supplies, and the achievement of regulatory requirements, at the cost of high level of inventory, higher costs and inventory write-off due to expiration or other reasons. In recent years this industry is facing major changes and challenges such as intense globalization processes, increased competition and innovations in technologies, which has broadened and deepened risks in supply chain. The paper reports the results of the study of the risk in distribution processes of Slovenian pharmaceutical companies, which was conducted among five companies and aims to draw attention to risks that arise in supply chain, to emphasize the importance of their management and to present a model for an effective assessment of risk in companies, developed at the Faculty of Logistics.
Keywords: distribucija; distribution; farmacevtska industrija; katalog tveganj; logistics; logistika; pharmaceutical industry; production companies; proizvodna podjetja; risk catalog; risk management; Slovenia; Slovenija; upravljanje tveganj